Mitochondrial quality control: a pathophysiological mechanism and potential therapeutic target for chronic obstructive pulmonary disease - Xu, Mengjiao; Feng, Peng; Yan, Jun; Li, Lei (Frontiers in Pharmacology, 2025)
Chronic obstructive pulmonary disease (COPD) is a prevalent chronic respiratory disease worldwide. Mitochondrial quality control mechanisms encompass processes such as mitochondrial biogenesis, fusion, fission, and autophagy, which collectively maintain the quantity, morphology, and function of mitochondria, ensuring cellular energy supply and the progression of normal physiological activities. However, in COPD, due to the persistent stimulation of harmful factors such as smoking and air pollution, mitochondrial quality control mechanisms often become deregulated, leading to mitochondrial dysfunction. Mitochondrial dysfunction plays a pivotal role in the pathogenesis of COPD, contributing toinflammatory response, oxidative stress, cellular senescence. However, therapeutic strategies targeting mitochondria remain underexplored. This review highlights recent advances in mitochondrial dysfunction in COPD, focusing on the role of mitochondrial quality control mechanisms and their dysregulation in disease progression. We emphasize the significance of mitochondria in the pathophysiological processes of COPD and explore potential strategies to regulate mitochondrial quality and improve mitochondrial function through mitochondrial interventions, aiming to treat COPD effectively. Additionally, we analyze the limitations and challenges of existing therapeutic strategies, aiming to provide new insights and methods for COPD treatment.